2016
DOI: 10.1002/adma.201603027
|View full text |Cite
|
Sign up to set email alerts
|

AuNP–Collagen Matrix with Localized Stiffness for Cardiac‐Tissue Engineering: Enhancing the Assembly of Intercalated Discs by β1‐Integrin‐Mediated Signaling

Abstract: A schematic for the mechanism of accelerating the assembly of intercalated discs (IDs) in cardiac myocytes regulated by gold nanoparticles (AuNPs) is presented. AuNPs with local nanoscale stiffness in the substrate activate β1-integrin signaling, which mediates the activation of integrin-linked kinase (ILK) and its downstream signal kinase by stimulating expression of the transcription factors GATA4 and MEF-2c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…The mechanistic study indicated that the integrin signaling pathway was involved in the modulation of CFs to the function of NRCMs. It has been demonstrated in literatures that the integrins not only act as a mechanosensors connecting the cytoskeleton to the extracellular matrix, but also play a central role in the regulation of cardiac electrical and mechanical junction proteins induced by mechanical stretch, and the β1‐integrin signaling pathway plays a role in conductive material–mediating cell–matrix interactions . It should be noted that PVA is a synthetic material and lacks sequences that are present in some biological macromolecules like gelatin and fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic study indicated that the integrin signaling pathway was involved in the modulation of CFs to the function of NRCMs. It has been demonstrated in literatures that the integrins not only act as a mechanosensors connecting the cytoskeleton to the extracellular matrix, but also play a central role in the regulation of cardiac electrical and mechanical junction proteins induced by mechanical stretch, and the β1‐integrin signaling pathway plays a role in conductive material–mediating cell–matrix interactions . It should be noted that PVA is a synthetic material and lacks sequences that are present in some biological macromolecules like gelatin and fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the MHC isoforms, PSC-CMs contain both isoforms of MLC (Zhang et al, 2013). PSC-CMs likewise exhibit low levels of expression of troponin isoforms, the protein involved in regulating myosin binding to actin, and alpha-actin isoforms, which contributes to the actin myofilaments, compared to adult CMs (Khan et al, 2015; Veerman et al, 2015; Li et al, 2016). Fetal CMs express mostly cTnT1 and cTnT2 which then switch to higher amounts of cTnT3 and cTnT4 during the neonatal stage and is abundant in adult CMs (Siedner et al, 2003).…”
Section: Maturation Differences Between Four Cardiomyocyte Developmenmentioning
confidence: 99%
“…Substrates with multiscale topography are designed to resolve this issue; the topography leads to variation in localized mechanical properties and associated micromechanical changes result in the manipulation of focal adhesion formation for the regulation of cell behaviors and functions ( Figure a) . For instance, Han's group developed a scaffold by mixing gold nanoparticles with collagen and the formative localized stiffness could efficiently regulate the assembly of intercalated discs through the β1 integrin‐mediated ILK/p‐AKT/GATA4 pathway . However, this method is relatively simple and has narrow application range.…”
Section: Hierarchical Hydrogel With Robust Micro/nanoscale Interfacesmentioning
confidence: 99%